Does working from home increases performance? A Study on Job Stress, Personal Outcomes and Job Meaningfulness - Saad, Carolina Waked (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM